Beyond the perception of present economic inequality: How people construe past, present and future wealth gaps - Andrea Scatolon; Silvia Galdi; Carmen Cervone; Lucia Mannetti; Anne Maass (PLoS ONE, 2026)
People tend to misperceive economic inequality levels in their country. However, studies investigating such misperceptions focused mainly on appraisals of present inequality. In two cross-sectional studies ( N total = 600), we investigated perceived past, present, and future wealth inequality in Italy, as well as accuracy in ranking EU countries by perceived wealth inequality. Confirming past literature, participants underestimated present levels of national wealth inequality. Results also showed the existence of a decline model in estimations of wealth inequality (i.e., optimism towards past, pessimism towards future), such that participants consistently expected an increase of future inequality (roughly corresponding to actual trends). Interestingly, participants were relatively accurate in ordering European countries, including Italy, with respect to levels of wealth inequality. We interpret these findings as reflecting a rational mechanism, where participants linearly project how wealth inequality grows (or declines) over time, and then plot their estimates for specific points in time on such linear projection. We therefore suggest that such schema prompt relative (rather than absolute) evaluations of wealth inequality, which leads to increased accuracy. We conclude that future interventions should accommodate people’s mental reconstruction of inequality.